Multifocal eosinophilic granuloma presenting as progressive brainstem and cerebellar dysfunction. Issue 8 (August 1994) - Fukazawa, T; Yanagihara, T; Hamada, K; Hamada, T
Abstract : A 55 year old woman with multifocal eosinophilic granuloma (MEG) is described. She developed facial numbness and twitching followed by slowly progressive cerebellar symptoms. Two years later polyuria and polydipsia were noted. A CT of the brain showed multifocal enhancing lesions, and MRI showed areas of hyperintensity on T2 weighted studies in the cerebellar peduncles, pons, and midbrain. Radiographs of the skull, pelvis, and long bones were normal, but a 99mTc diphosphonate bone scan and MRI showed bone lesions compatible with granuloma. The diagnosis of MEG was made by bone biopsy. This is believed to be the first case of MEG with such unusual clinical profiles and radiographical findings. Skeletal surveys are indicated for patients with unexplained focal or multifocal inflammatory changes in the cerebellum.